(3GdbhGfjf GdSdWGfjI aj GdUjOs - (3GdbGSe Hf Ydj Hf GdMSjf GdgGTej GdRjfHj, CHh fUQ,J (B563 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QGRb GdCfGe hNGdb GdCfYeGe , eOHQ GdNdGFb HMceJg , heUQa GdBbOGQ ajge HeTjFJg s
(3BNQgG (B:s
(3hdOhdJg GdbGgQg hBjGeg GdfVQg GdRGgQg HGdHbGA hGdNdhO hGdYR GdOGFe s
(3HQSe GdNdjaI GdeSJfLO HGddg GdYHGSi GdeJhai SfI (B884s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B178s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe fYGQa YGeg (B- (3U (B28 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdaGJM HGSJGfHhd (B(4508) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs